The Role of Social Media in Digital Marketing Strategy at PT Desain Sarana Intermatra Jakarta with the Peso Model - Zahda Ulfah Alifiani; Dian Ajeng Kirana (TUMATA: Journal of Arts and Cultural Management, 2026)
PT Desain Sarana Intermatra, an interior design company based in Jakarta, has been trying to grow its business through digital marketing in recent years. The purpose of this study was to look at how businesses are using digital marketing strategies based on the PESO (Paid, Earned, Shared, and Owned) framework and find which areas need to be strengthened. The research process was carried out using a qualitative method, where data was collected through in-depth interviews with the company's internal parties. The data obtained was then analyzed by mapping digital marketing activities into each element of the PESO Model to see the level of utilization and integration. The results show that owned media (such as websites and digital portfolios) and shared media (such as active social media) are the main pillars of digital marketing. On the other hand, paid media (such as paid advertising) is still used unevenly and unmeasurably. The resources obtained (testimonials, reviews, and coverage) have also not been used effectively, especially to increase credibility and reach. To achieve synergy in marketing communication, the analysis shows that budgets for advertising must be allocated consistently, a review management system must be created, and a Paid–Shared–Owned–Earned system must be combined.